Assessing the Effectiveness of the Lithuanian Non-Word Repetition Test as a Screening Tool for Dyslexia - Krivickaitė-Leišienė, Eglė; Kavaliauskaitė-Vilkinienė, Viktorija (Pedagogika, 2025)
This paper focuses on the ability of children with dyslexia ( 8;9) and TD children ( 8;2) to repeat Lithuanian non-words. Research shows that dyslexic children have difficulties with phonological processing tasks, such as encoding phonological information, retaining it in VPSTM for a certain period, and retrieving it. The results of this study provide valuable insights into the phonological difficulties of dyslexic children and may contribute to the development of more effective support.